Ostreid herpesvirus 1 latent infection and reactivation in adult Pacific oysters, Crassostrea gigas - Konstantin Divilov; Xisheng Wang; Alexandra E. Swisher; Peyton C Yeoman; Maxwell Rintoul; Gary B. Fleener; Blaine Schoolfield; Chris Langdon; Ling Jin (Virus Research, 2024)
Ostreid herpesvirus 1 (OsHV-1) is one of the most economically important pathogens of Pacific oysters. Understanding the pathogenesis of this virus is critical to developing tools to control outbreaks on shellfish farms. OsHV-1 is genetically related to vertebrate herpesviruses, which have a lytic and a latent stage, with the latent stage capable of being reactivated to the lytic stage. Here, OsHV-1 latency in Pacific oysters was investigated in experimentally and naturally infected oysters. Lytic infection in one-year-old oysters injected with the Tomales Bay strain of OsHV-1 was detectable between 1 and 4 days post-injection (dpi) but was not detectable after 5 dpi. The injected oysters shed 1 × 102 to 1 × 104 DNA copies/ml into the water during the 4-day acute phase. Lytic shedding was not detectable in two-year-old oysters injected similarly with the same strain of OsHV-1; however, the OsHV-1 genome was detectable by qPCR in the adductor muscle, gill, mantle, and hemocytes within the first 3 dpi, after which it became undetectable. No OsHV-1 was detectable in the adductor muscle, gill, or mantle from experimentally infected oysters on days 15 and 21 post-injection or from oysters sampled 9 months after surviving an OsHV-1 mortality event; however, OsHV-1 DNA could be detected in hemocytes of both experimentally infected oysters at 21 dpi and naturally infected oysters using nested PCR. In addition, lytic viral gene transcription was detectable in hemocytes of experimentally infected oysters between 1 and 21 dpi and in hemocytes of naturally infected oysters. Furthermore, OsHV-1 reactivation from latency was induced in experimentally infected oysters at 21 dpi and in naturally infected oysters 12 months after an OsHV-1 outbreak.